Dedication: Dirk R. Vuylesteke: Musa scientist and Humanitarian - Ortíz, R. (2001)
This volume of Plant Breeding Reviews is dedicated to the memory of Dirk R. Vuylsteke who died tragically in an air crash on January 30, 2000, while actively engaged in his live long passion, the betterment of efforts to fight hunger and poverty in tropical Africa. Dirk was a leading Musa scientist who contributed to and led a wide range of development projects in tropical Africa. He dedicated all his professional life to plantain and banana improvement for the small landholders of sub-Saharan Africa. Vuylsteke’s most notable contributions were in the field of Musa agronomy, taxonomy, tissue culture, breeding, and genetics. He was an accomplished, successful, and popular research manager in a diverse array of programs and projects that he led and the committees in which he participated at the International Institute of Tropical Agriculture (IITA), as well as in other national and regional committees in Africa. Dirk Vuylsteke, will continue to be a source of inspiration for the new generation of scientists joining international agricultural research for development.